Pyrolysis of 1,2-dichloroethane over Ni-Cr catalyst at resistive heating; Reaction Kinetics, Mechanisms and Catalysis; Vol. 120, iss. 2 - Bauman Y. I. Yury; Sigaeva S. S. Svetlana; Mishakov I. V. Iljya Vladimirovich; Vedyagin A. A. Aleksey Anatolievich; Tsyrulnikov P. G. Pavel; Korneev D. V. Denis; Buyanov R. A. Roman (2017, 2017)
Title screen